Formation Structural Phase Gradients in Rail Steel During Long-Term Operation; IOP Conference Series: Materials Science and Engineering; Vol. 112 : Fundamental Aspects of Rare-earth Elements Mining and Separation and Modern Materials Engineering (REES-2015) - Ivanov Yu. F. Yuriy Fedorovich; Morozov K. V.; Peregudov O.; Gromov V. E.; Popova N. A.; Nikonenko E. N. (2016, 2016)
Title screen